2017
DOI: 10.1093/geroni/igx003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Lichtenberg Financial Decision Screening Scale

Abstract: The scarcity of empirically validated assessment instruments continues to impede the work of professionals in a number of fields, including medicine, finance, and estate planning; adult protective services; and criminal justice—and, more importantly, it impedes their ability to effectively assist and, in some case, protect their clients. Other professionals (e.g., legal, financial, medical, mental health services) are in a position to prevent financial exploitation and would benefit from access to new instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…As a result of the small percentage, Intellectual Factor subscale items were only used in convergent validity analyses, since the lack of variance precluded use in CFA. In our previous work, however (Lichtenberg et al, in press) the Intellectual Factor subscale was found to be reliable and valid.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…As a result of the small percentage, Intellectual Factor subscale items were only used in convergent validity analyses, since the lack of variance precluded use in CFA. In our previous work, however (Lichtenberg et al, in press) the Intellectual Factor subscale was found to be reliable and valid.…”
Section: Resultsmentioning
confidence: 70%
“…Risk scores for the contextual variables and each subscale are then added. The risk score for the intellectual factors subscale follows a validated seven-item algorithm—or alternatively, a simple count of discrepancies between items is used (see Lichtenberg et al, in press). Each participant will have six scores: the five subscale risk scores and a total risk score.…”
Section: Methodsmentioning
confidence: 99%
“…The E-IOA, EAI and the EPAS were validated in patients admitted to a hospital, an emergency department and in long-term care (nursing home), respectively. Seven new instruments have been published since June 2015: Risk on Elder Abuse and Mistreatment Instrument (REAMI), 33 Assessment Tool for Domestic Elder Abuse (ATDEA), 34 QualCare Scale, 35 Elder Abuse Risk Assessment and Evaluation (EARAE) tool, 36 short-form measures of four types of elder abuse (financial, emotional/ psychological, physical, neglect), 37 the Lichtenberg Financial Decision Screening Scale (LFDSS), 38 and the Family Members Mistreatment of Older Adults Screening Questionnaire (FAMOASQ). 39 The REAMI, a questionnaire that contains 22 items, was developed and tested using a mixed method design.…”
Section: G Nurses) and Social Workersmentioning
confidence: 99%
“…37 The LFDSS was introduced in 2016 aiming to prevent financial exploitation. 38 This scale is taken orally; because it is a rating scale the interviewer's judgment is critical. 38 However, the LFDSS can be easily taught to professionals of the Adult protection services (APS).…”
Section: G Nurses) and Social Workersmentioning
confidence: 99%
See 1 more Smart Citation